Capacity Investigations of MIMO Systems in Correlated Rician Fading Channel Using Statistical Clustered Modelling - Mangoud, Mohab A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper the capacity of MIMO systems is investigated for different realistic propagation scenarios in Rician fading channel. A nonparametric stochastic model is presented and is used to develop the spatial fading correlation. Uplink statistical MIMO channel is assumed with Laplacian angular energy distributed over multi-clusters situations. Radio waves that are gathered in several clusters distributed over the space domain are assumed to exhibit different power profiles. Capacity investigations for both uniform linear array (ULA) and uniform circular array (UCA) for single cluster and multi-clustered assumptions are presented. The optimum selections of number of elements and spacing between elements are discussed for different values of Angle of Arrival (AoA) and Azimuth Spread (AS). Also, the impact of K factor of the Rician distribution for single and multi-clusters environments is studied under different propagation scenarios.